SARS‐CoV‐2 outbreak in Iran: The dynamics of the epidemic and evidence on two independent introductions. Issue 3 (22nd May 2021) - Fattahi, Zohreh; Mohseni, Marzieh; Jalalvand, Khadijeh; Aghakhani Moghadam, Fatemeh; Ghaziasadi, Azam; Keshavarzi, Fatemeh; Yavarian, Jila; Jafarpour, Ali; Mortazavi, Seyedeh Elham; Ghodratpour, Fatemeh; Behravan, Hanieh; Khazeni, Mohammad; et al.
Abstract: The SARS‐CoV‐2 virus has been rapidly spreading globally since December 2019, triggering a pandemic, soon after its emergence. While Iran was among the first countries confronted with rapid spread of virus in February 2020, no real‐time SARS‐CoV‐2 whole‐genome tracking in early phase of outbreak was performed in the country. To address this issue, we provided 50 whole‐genome sequences of viral isolates ascertained from different geographical locations in Iran during March–July 2020. The corresponding analysis on origins, transmission dynamics and genetic diversity of SARS‐CoV‐2 virus, represented at least two introductions of the virus into the country, constructing two major clusters defined as B.4 and B.1*. The first entry of the virus might have occurred around very late 2019/early 2020, as suggested by the time to the most recent common ancestor, followed by a rapid community transmission that led to dominancy of B.4 lineage in early epidemic till the end of June. Gradually, reduction in dominancy of B.4 occurred possibly as a result of other entries of the virus, followed by surge of B.1* lineages, as of mid‐May. Remarkably, variation tracking of the virus indicated the increase in frequency of D614G mutation, along with B.1* lineages, which showed continuity till October 2020. The increase in frequency of D614G mutation and B.1* lineages from mid‐May onwards predicts a rapid viral transmission that may push the country into a critical health situation followed by a considerable change in composition of viral lineages circulating in the country.